Case Report: Unusual Presentations of Loss-of-Function Mutations of the Calcium-Sensing Receptor - Palmieri, Serena; Grassi, Giorgia; Guarnieri, Vito; Chiodini, Iacopo; Arosio, Maura; Eller-Vainicher, Cristina (Frontiers in Medicine, 2022)
Background: In recent years, heterozygous loss-of-function mutations of the Calcium Sensing Receptor gene (CaSR) were implicated in different hypercalcemic syndromes besides familial hypocalciuric hypercalcemia (FHH), including neonatal severe primary hyperparathyroidism (NSHPT) and primary hyperparathyroidism (PHPT). Cases presentation: Here we describe two unusual presentations of heterozygous inactivating CaSR mutations. Case 1: a case of NSHPT due to a de novo, p.(ArgR185Gln) CaSR mutation and successfully treated with cinacalcet monotherapy for 8 years until definitive surgical resolution. Case 2: a 37 years-old woman with PHPT complicated with hypercalcemia and nephrocalcinosis with a novel heterozygous p.(Pro393Arg) CaSR mutation and cured with parathyroidectomy. Conclusions: These cases reinforce the fact that the clinical spectrum of inactivating mutations of the CaSR has widened and, although carrying a mutation suggestive of FHH, some patients may have different clinical phenotypes and complications requiring individualized therapies.